A Novel Incentive Mechanism with Government Subsidy for the Key Technologies R&D of New Energy Automobile Industry. (29th September 2021) - He, Ru; Zheng, Chui-Yong; Zhao, Huan-Huan
Abstract : The key technology research and development (R&D) of new energy automobile industry is a collaborative innovation activity of multi-innovation subjects, and how to set up effective incentive mechanisms and safeguards to stimulate innovative subjects and urge them to invest in corresponding efforts is crucial to ensure the success of key technologies R&D in the new energy automobile industry. To solve the incentive problem of key technology R&D of new energy automobile industry, considering government subsidy and the risk attitude of government and innovation subject, from the perspective of stakeholder negotiation and system coordination, introduce the minimum-cost consensus method into grey target decision-making and set constraint conditions to ensure a stable and effective incentive method. Then use a case to verify the effectiveness and rationality of the proposed model.